Evaluation of the hepatotoxicity of Psoralea corylifolia L. based on a zebrafish model - Gao, Shu-Yan; Zhao, Jing-Cheng; Xia, Qing; Sun, Chen; Aili, Maimaiti; Talifu, Ainiwaer; Huo, Shi-Xia; Zhang, Yun; Li, Zhi-Jian (Frontiers in Pharmacology, 2024)
Psoralea corylifolia L. (FP) has received increasing amounts of attention due to its potential hepatotoxicity. METHODS: In this study, zebrafish were treated with different concentrations of aqueous extract of FP (AEFP; 40, 50, or 60 μg/mL), and the hepatotoxic effects of tonicity were determined by the mortality rate, liver morphology, fluorescence area and intensity of the liver, biochemical indices, and pathological tissue staining. The mRNA expression of target genes in the bile acid metabolic signalling pathway and lipid metabolic pathway was detected by qPCR, and the mechanism of toxicity was initially investigated. AEFP (50 μg/mL) was administered in combination with FXR or a PPARα agonist/inhibitor to further define the target of toxicity. RESULTS: Toxic effect experiments showed that, compared with no treatment, AEFP administration resulted in liver atrophy, a smaller fluorescence area in the liver and a lower fluorescence intensity (P < 0.05); ALT, AST and γ-GT were significantly elevated in zebrafish (P < 0.01), and TBA, TBIL, TC, TG, LDL-C and HDL-L were elevated to different degrees (P < 0.05); and increased lipid droplets in the liver appeared as fatty deposits. Molecular biological validation revealed that AEFP inhibited the expression of the FXR gene, causing an increase in the expression of the downstream genes SHP, CYP7A1, CYP8B1, BSEP, MRP2, NTCP, PPAR-γ, ME-1, SCD-1, LPL, CPT-1, and CPT-2 and a decrease in the expression of PPAR-α (P < 0.05). Conclusions: This study demonstrated that tonic acid extracts are hepatotoxic to zebrafish through the inhibition of FXR and PPARα expression, thereby causing bile acid and lipid metabolism disorders.